2, 5, 9, 14, 20, 27, …

What is the general nth term?

Why is the general term a quadratic expression?

The sequence follows the recurrence relation:

a_1 = 2
a_2 = a_1 + 3
a_3 = a_2 + 4
a_4 = a_3 + 5
a_n = a_(n-1) + (n+1)
= a_(n-2) + (n) + (n+1)
= a_(n-3) + (n-1) + (n) + (n+1) —- (involves a summation of ‘n’ terms of b_n = n+1)
= a_1 + 3 + 4 + …. + (n+1)
= 2 + (n-1)(n+4)/2

Advertisements
This entry was posted in Uncategorized. Bookmark the permalink.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s